Burnout among public primary school teachers in Dire Dawa administrative region, Ethiopia - Mamo, Daniel (Frontiers in Education, 2022)
The study aimed to assess the level of professional burnout and the effect of demographic variables among primary school teachers in Dire Dawa town. A cross-sectional survey research design on data collected using teacher burnout scale from 211 teachers was conducted. Data was analyzed using descriptive and inferential statistics. It was revealed that primary school teachers in the administration experience high professional burnout and male older teachers with many years of service experience burnout. Educational qualification showed no relationship with the experience of burnout. Teachers’ gender is correlated with career satisfaction and coping with job stress while experience is correlated with perceived administrative support and attitude toward students. Moreover, the change in burnout experience of primary school teachers could be explained by socio-demographic variables. Thus, it was recommended that school leaders should introduce urgent interventions to help teachers cope with their job stress and burnout.